A hypoeutectic high-entropy alloy with hierarchical microstructure for high-temperature application. (15th July 2023) - Liu, Linxiang; Wang, Zhijun; Wu, Qingfeng; Jia, Yuhao; Xu, Q.; He, Feng; Li, Junjie; Wang, Jincheng
Abstract: Dual-phase high entropy alloys have great potential for high-temperature applications. In this work, a hypoeutectic Ni41.8 Co19 Cr10 Fe10 Al15 Ti2 Mo2 Hf0.1 B0.1 high-entropy superalloy consisting of FCC and B2 matrix was developed with superior high-temperature mechanical properties. After aging, high-density L12 particles precipitated in the FCC matrix, while lath-shaped FCC and Cr-rich σ phases precipitated in the B2 matrix. The hierarchical microstructure contributed to the high yield strength of ∼1.1 GPa MPa at 25 °C and ∼614 MPa at 800 °C. In addition, the B2 matrix with a serrated phase boundary retarded crack nucleation and propagation, leading to an excellent tensile elongation of ∼26.1% at 800 °C. These results are significant to the development of high-performance hypoeutectic alloys for application over a wide temperature range. Graphical abstract: Image, graphical abstract